The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fpsyt.2020.518961
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Consequences of Female Infertility in Iran: A Meta-Analysis

Abstract: Background: Although not a life-threatening condition, infertility does influence various aspects of life. Based on a meta-analysis of the relevant literature, the aim of this study is to identify the psychosocial consequences of infertility in Iranian women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 72 publications
1
12
1
Order By: Relevance
“…This was contradictory to findings from researches done in developing countries in previous decades but similar to latest research on infertility associated behaviors. 34 A study from Karachi reported a lower mean for all subscales of FertiQoL as compared to our findings. 33 Our study's total FertiQoL score mean 66 was higher than this.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…This was contradictory to findings from researches done in developing countries in previous decades but similar to latest research on infertility associated behaviors. 34 A study from Karachi reported a lower mean for all subscales of FertiQoL as compared to our findings. 33 Our study's total FertiQoL score mean 66 was higher than this.…”
Section: Discussioncontrasting
confidence: 67%
“…[10][11][12][13] Infertile couples have to face a wide range of psychological influences so there arises the need for psychological support and counseling of infertile couples. 34 This was a cross-sectional study focusing on females due to convenience of their presence in infertility clinics as compared to men. A couple based approach may be better for future studies so both can give an insight into quality of life and its subscales.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the environmental toxin exposure, and also prenatal exposure to commonly used chemicals, e.g. phthalates, may increase the risk of both infertility and neoplasm in men ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been reported that the fear of infertility and its consequences may influence help-seeking behaviors in men, which may trigger diseases in later life ( 30 ). The experience of infertility may negatively impact on personal health behaviors ( 31 ) and in some contexts, it may hinder taking further actions to prevent health-related problems or seek appropriate treatments ( 29 ). It has been hypothesized that unhealthy behaviors may predispose infertile patients to cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Literature is replete with evidence that infertility is associated with a wide-range of psychosocial consequences in women, including poor quality of life and marital relationships, depression, anxiety, decreased self-esteem, victims of violence, irrational thoughts, feelings of apprehensions and rejection, social stigma, somatization disorders, sexual dysfunction, and many more [6][7][8][9][10][11][12]. Significant association of psychosocial wellbeing has been found with age, occupation, education, and lack of social support [13,14].…”
Section: Introductionmentioning
confidence: 99%